İcra-iflas hukukunda disiplin ve tazyik hapsi - Altınöz, Ünal (My University, 2019)
İcra ve İflas Kanunu, 16. Babında disiplin ve tazyik hapsi yaptırımı öngören eylemlere yer vermektedir. İş bu çalışmamızda, disiplin ve tazyik hapsinin tarihsel incelemesi gerçekleştirildikten sonra genel hatları ile İcra ve İflas Hukuku’nun önemine, hukuk sistemindeki yerine ve cezai hükümlerine işaret edilmiştir. Akabinde disiplin ve tazyik hapsi özelinde bahsi geçen kavramlara ilişkin inceleme gerçekleştirilmiş ve disiplin ve tazyik hapsinin amacına değinilmiştir. Disiplin ve tazyik hapsinin hukuk sisteminde yeri inkâr edilemez olan temel ilkeler ile ilişkisi ayrıca incelenmiştir. Hukuki metinlerde farklı görüşlere yer verildiği tahlil edilen disiplin ve tazyik hapsinin hukuki niteliğinin tespitine ilişkin ayrı bir inceleme gerçekleştirilmiştir. Bu incelemede, ele alınan farklı görüşler değerlendirmeye alınmış ve sonucunda disiplin ve tazyik hapsi için hukuki nitelik belirlemesi gerçekleştirilmiştir. Bu belirlemenin neticesinde söz konusu niteliğin sonuçlarına işaret edilmiştir. Birçok kez Anayasa’ya aykırılığı ileri sürülen disiplin ve tazyik hapsi yaptırımından yola çıkılarak, disiplin ve tazyik hapsinin Anayasa’ya aykırılık-uygunluk değerlendirmesi yapılmıştır. Bu değerlendirmelerin ardından kanunda disiplin ve tazyik hapsi öngörülen eylemler genel hatları ile incelenmiştir. Söz konusu eylemlerin disiplin ve tazyik hapsi yaptırımı bakımından değerlendirmesinin hangi kurallara riayet edilerek hükme bağlanacağının belirlenmesi için yargılama usulü genel hatları ile incelenmiştir.

The Law on Enforcement and Bankruptcy provides for acts of disciplinary and preventive detention under Article 16. In this study, after the historical examination of disciplinary and preventive detention, the importance of the law of execution and bankruptcy and its place in the legal system and its penal provisions were pointed out. After that, an investigation was made on the concepts of disciplinary and preventive detention and the aim of disciplinary and preventive detention was mentioned. The roles of disciplinary and preventive detention in the legal system and its relation to the basic principles which cannot be denied have also been examined. A separate review was carried out to determine the legal nature of the disciplinary and preventive detention which was analyzed in the legal texts. In this review, different opinions were taken into consideration and as a result, legal qualification was determined for disciplinary and preventive detention. As a result of this determination, the results of this qualification have been pointed out. The unconstitutionality-conformity assessment of the disciplinary and preventive detention was carried out on the basis of this disciplinary and preventive detention, which was allegedly violated many times. After these evaluations, the actions of the law, foreseeing disciplinary and preventive detention, have been examined in general terms. In order to determine the rules of assessment of these actions in terms of the sanction of disciplinary and preventive detention, thejudicial procedure has been examined in general terms.
Keywords: Disciplinary Confinement; Disiplin Hapsi; İcra ve İflas Hukuku; Preventive Detention; Tazyik Hapsi Execution and Bankruptcy Law